Pengaruh Net Profit Margin Dan Total Asset Turnover Terhadap Pertumbuhan Laba Pada Perusahaan Otomotif Yang Terdaftar Di Bursa Efek Indonesia Periode 2016-2020 - Widya Natasya; Yuserizal Bustami; Elex Sarmigi; Alex Wissalam Bustami; Dafiar Syarif; Martina Nofra Tilopa (Journal Islamic Economic and Bussines Studies, 2022)
Research Objectives: This study aims to determine the effect of two X variables, namely Net Profit Margin (X1) and Total Asset Turnover (X2) on Profit Growth (Y) on the Indonesia Stock Exchange with 30 samples from 6 automotive companies listed on the Indonesia Stock Exchange. Design/Methodology/Research Approach: This study uses a type of research using time series. This research is a causal type of research with a quantitative approach. The data analysis method used is multiple linear regression with SPSS 23 software. Research Results: The results showed that the t-test results of the Net Profit Margin (X1) variable showed tcount > ttable, namely 4.043> 2.050 with a Sig value of 0.000 <0.05, it can be concluded that Ha1 is accepted and Ha0 is rejected. From the results of the t test for the Total Asset Turnover (X2) variable, it shows that tcount > ttable is -0.342 < 2.050 with a Sig value of 0.735 > 0.05, it can be concluded that Ha2 is rejected and H0 is accepted.